2019
DOI: 10.1002/wer.1140
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate residual as a key parameter to efficiently control partial denitrification coupling with anammox

Abstract: Despite the increased research efforts, full-scale implementation of shortcut nitrogen removal strategies has been challenged by the lack of consistent nitrite-oxidizing bacteria out-selection. This paper proposes an alternative path using partial denitrification (PdN) selection coupled with anaerobic ammonium-oxidizing bacteria (AnAOB). A nitrate residual concentration (>2 mg N/L) was identified as the crucial factor for metabolic PdN selection using acetate as a carbon source, unlike the COD/N ratio which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 50 publications
8
88
0
Order By: Relevance
“…However, under the 0.5 mg/L DO scenario, the AMX activities increase over the process train before each influent feeding, and each influent feeding noticeably reduces the AMX activities. This is because in the model framework, can only be conserved for anammox if organic carbon is not enough for further denitrification of , and the simulation outcome conforms to experimental observations that PdN requires delicate controls of organic carbon addition (Cao et al 2013 ; Du et al 2019b ; Le et al 2019 ). The contrast between the 0.1 and 0.5 mg/L DO scenarios also demonstrates that availability (pre-ready versus immediate generation among competitive environment) has a pronounced impact on AMX activities (Le et al 2019 ; Jia et al 2020 ).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…However, under the 0.5 mg/L DO scenario, the AMX activities increase over the process train before each influent feeding, and each influent feeding noticeably reduces the AMX activities. This is because in the model framework, can only be conserved for anammox if organic carbon is not enough for further denitrification of , and the simulation outcome conforms to experimental observations that PdN requires delicate controls of organic carbon addition (Cao et al 2013 ; Du et al 2019b ; Le et al 2019 ). The contrast between the 0.1 and 0.5 mg/L DO scenarios also demonstrates that availability (pre-ready versus immediate generation among competitive environment) has a pronounced impact on AMX activities (Le et al 2019 ; Jia et al 2020 ).…”
Section: Resultssupporting
confidence: 70%
“…In reality, PdN is more controllable than PN, but maintaining PdN might also require proper types of organic carbon, e.g., acetate or glycerol (Cao et al 2013 ). In a PdNA study carried by the District of Columbia Water and Sewer Authority (DC Water), it is demonstrated that the organic carbon from raw wastewater should be depleted before PdN can occur in a controllable manner, and a delicate control of organic carbon addition should also be implemented depending on the level in the PdNA unit (Le et al 2019 ). In this current model-based study, the depressed AMX activities by each influent feeding under the 0.5 mg/L DO scenario suggest the need for an even more distributed organic carbon dosage to lower the negative effect from organic loading shocks, e.g., use intermittent carbon source addition to prevent thorough denitrification (Du et al 2019a ), similarly like intermittent aeration is often used to promote PN by preventing full nitrification (Corbalá-Robles et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilot-scale application of ammonia vs. nitrate-nitrite DO control algorithm using dynamic alpha adjustment based on influent inorganic nitrogen demonstrated the potential for ANNUAL LITERATURE REVIEW reducing aeration and carbon requirements and meeting an effluent total inorganic nitrogen of 4 mg/L based on a partial denitrification-anoxic ammonia-oxidizing bacteria shortcut-nitrogen removal process (Le, Fofana, et al, 2019). Le, Peng, et al (2019) reported the potential for more than 50% reduction in supplemental carbon during operation of a partial denitrification-anoxic ammonia oxidation pilot process controlled by ammonia vs. nitrate-nitrite DO control.…”
Section: Control and Automationmentioning
confidence: 99%